UJI BERBAGAI DIAMETER PULI PADA ALAT PENCETAK TERASI (Pulley Diameter Test on the Shrimp Paste Molder) - Untung Utoyo; Saipul Bahri Daulay; Ainun Rohanah (Universitas Sumatera Utara, 2017)
ABSTRACT Shrimp paste molder that had been designed previously was not effective in process, so the author suspect that the performance of the machine will be better if pulley with right diameters is used. The research’s purpose is to examine the effect of various pulley diameter on the effective capacity, yield, and the percentage of left material of the shrimp paste molder. This research was conducted in November 2015 to January 2016 in the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra, Medan. The parameter sobserved were effective capacity, yield and the percentage of left material on the shrimp paste molder. The result shows that the highest effective capacity was 106,41 kg/hour at treatment D1 with 2 inch pulley diameter, the highest yield was treatment D1with 2 inch pulley diameter (66,6%), and the percentage of material left behind was the lowest at treatment of D1 with 2 inch pulley diameter (33,4%). From Duncan Multiple Range Tests it was found that the pulley diameter had highly significant effect on the effective capacity and had significant effect on yield and percentage of material left behind. Keywords: Molder, Pulley, Shrimp Paste ABSTRAK Alat pencetak terasi yang telah dirancang sebelumnya dinilai kurang efektif dalam pengolahannya, sehingga penulis menduga akan terjadi perubahan kinerja alat apabila digunakan puli dengan diameter yang tepat. Penelitian ini bertujuan untuk menguji pengaruh berbagai diameter puli terhadap kapasitas efektif alat, rendemen, dan persentase bahan tertinggal pada alat pencetak terasi. Penelitian ini dilakukan pada bulan November 2015 hingga Januari 2016 di Laboratorium Keteknikan Pertanian, Fakultas Pertanian Universitas Sumatera Utara, Medan. Parameter yang diamati yaitu kapasitas efektif alat, rendemen dan persentase bahan tertinggal. Dari hasil penelitian diperoleh kapasitas efektif alat tertinggi terdapat pada perlakuan D1 yaitu dengan diameter puli 2 inci sebesar 106,41 kg/jam, rendemen tertinggi terdapat pada perlakuan D1 yaitu dengan diameter puli 2 inci sebesar 66,6%, dan persentase bahan tertinggal yang terendah terdapat pada perlakuan D1 yaitu dengan diameter puli 2 inci sebesar 33,4%. Dari pengujian DMRT diperoleh bahwa diameter puli pada alat pencetak terasi memberikan pegaruh berbeda sangat nyata terhadap kapasitas efektif alat dan memberikan pengaruh berbeda nyata terhadap rendemen dan persentase bahan tertinggal. Kata kunci: Alat Pencetak, Puli, Terasi